High-Fat Diet and Feeding Regime Impairs Number, Phenotype, and Cytotoxicity of Natural Killer Cells in C57BL/6 Mice - Spielmann, Julia; Naujoks, Wiebke; Emde, Matthias; Allweyer, Martin; Kielstein, Heike; Quandt, Dagmar; Bähr, Ina (Frontiers in Nutrition, 2020)
Overweight and obesity are major public health challenges worldwide. Obesity is associated with a higher risk for the development of several cancer types, but specific mechanisms underlying the link of obesity and cancer are still unclear. Natural killer (NK) cells are circulating lymphoid cells promoting the elimination of virus-infected and tumor cells. Previous investigations demonstrated conflicting results concerning the influence of obesity on functional NK cell parameters in small animal models. The aim of the present study was to clarify potential obesity-associated alterations of murine NK cells in vivo, implementing different feeding regimes. Therefore, C57BL/6 mice were fed a normal-fat diet (NFD) or high-fat diet (HFD) under restrictive and ad libitum feeding regimes. Results showed diet and feeding-regime dependent differences in body weight, visceral fat mass and plasma cytokine concentrations. Flow cytometry analyses demonstrated significant changes in total cell counts as well as frequencies of immune cell populations in peripheral blood comparing mice fed NFD or HFD in an ad libitum or restrictive manner. Mice fed the HFD showed significantly decreased frequencies of total NK cells and the mature CD11b+CD27+ NK cell subset compared to mice fed the NFD. Feeding HFD resulted in significant changes in the expression of the maturation markers KLRG1 and CD127 in NK cells. Furthermore, real-time PCR analyses of NK-cell related functional parameters in adipose tissue revealed significant diet and feeding-regime dependent differences. Most notable, real-time cytotoxicity assays demonstrated an impaired cytolytic activity of splenic NK cells toward murine colon cancer cells in HFD-fed mice compared to NFD-fed mice. In conclusion, our data demonstrate that feeding a high-fat diet influences the frequency, phenotype and function of NK cells in C57BL/6 mice. Interestingly, restricted feeding of HFD compared to ad libitum feeding resulted in a partial prevention of the obesity-associated alterations on immune cells and especially on NK cells, nicely fitting with the current concept of an advantage for interval fasting for improved health.